2022
DOI: 10.29026/oea.2022.210093
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric χ<sup>(2)</sup> metasurfaces: recent progress

Abstract: Optical metasurfaces, i.e. arrays of nanoantennas with sub-wavelength size and separation, enable the manipulation of light-matter interactions in miniaturized optical components with no classical counterparts. Six decades after the first observation of the second harmonic generation (SHG) in bulk crystals, these devices are expected to break new ground in the field of nonlinear optics, shifting the focus from the phase matching approach achieved within long propagation distances to that of near-field resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(20 citation statements)
references
References 163 publications
0
20
0
Order By: Relevance
“…In this context, the first demonstrations were carried out by considering the metasurface as a passive object where the output light wavelength is the same as the incoming one [60,61]. However, dielectric materials such as GaAs and AlGaAs have also a strong nonlinear response of the second order with higher efficiency with respect to plasmonic nano-antenna [62]. In such high-refractive index materials it is thus possible to efficiently generate a signal at a different frequency (i.e.…”
Section: Liquid Crystal-embedded Nonlinear Dielectric Metasurfacementioning
confidence: 99%
“…In this context, the first demonstrations were carried out by considering the metasurface as a passive object where the output light wavelength is the same as the incoming one [60,61]. However, dielectric materials such as GaAs and AlGaAs have also a strong nonlinear response of the second order with higher efficiency with respect to plasmonic nano-antenna [62]. In such high-refractive index materials it is thus possible to efficiently generate a signal at a different frequency (i.e.…”
Section: Liquid Crystal-embedded Nonlinear Dielectric Metasurfacementioning
confidence: 99%
“…18 With the development of fabrication methods, new-type ADM metasurfaces have been designed to support Fano resonances, [19][20][21][22][23] anapole mode, 24 bound states in the continuum (BIC), [25][26][27] and strong coupling. 28 ADMs play a crucial role in numerous potential applications, such as optical sensors, 2-6 nonlinear optics, 29,30 imaging, 31 and surface enhanced Raman spectroscopy (SERS). [32][33][34][35] The superiority of dielectric nanoparticles has been experimentally verified by comparing them with plasmonic nanostructures for sensing performance.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Coppens Z J et al found that AZO metasurfaces possessed significant infrared localized properties [9] . The LSPP of AZO metasurfaces has the following unique advantages [10][11][12][13][14][15] : (1) The dispersion satisfies the Drude-Lorentz model and exhibits good dielectric properties in the ultraviolet and visible regions, whereas it exhibits better metallic properties in the infrared region; (2) LSPP is mainly concentrated in the infrared wavelength band; (3) the carrier concentration can be controlled; (4) the dispersion is low in the infrared region. Therefore, this paper took the study of thermal radiation characteristics of metasurfaces as the exploration direction and deeply discussed the factors affecting the performance of metasurfaces.…”
Section: Introductionmentioning
confidence: 99%